Insight into the relationship between microorganism communities and flavor quality of Chinese dry-cured boneless ham with different quality grades. (December 2022) - Li, Zimu; Wang, Ying; Pan, Daodong; Geng, Fang; Zhou, Changyu; Cao, Jinxuan
Abstract: Microorganisms played a key role in developing the flavor quality, while few studies focused on the relationship between microbial diversity and flavor quality of dry-cured boneless ham. To explore the relationship, sensory evaluation, lipases, microorganism communities, free fatty acids and volatile compounds were investigated in dry-cured boneless ham with different quality grades (NS, WS and GS groups); the correlation between cored microbes and crucial volatiles was further evaluated by metabolic network analysis. GS group showed the highest scores in aroma and overall acceptance among three groups. The highest values of phospholipase activities (7.88 U*g −1 protein) were shown in GS group, while the lowest values of TBARS (0.93 mg/kg) were observed in GS among three groups. High-throughput sequencing revealed that fungi showed the most various among three groups; Xerochrysium, Aspergillus, Penicillium and Debaryomyces were the most genera in GS. SPME-GC-MS revealed that GS showed higher contents and numbers in volatiles than other groups; aldehydes and furans were intensely response to the variations of volatiles among these groups. Metabolic pathway further revealed that several key species derived from Penicillium and Aspergillus accelerated the formation of volatiles by β-lipoxidation and Strecker degradation. These results indicated that molds could be the major contributors in developing and differentiating the flavor quality of Chinese dry-cured boneless ham. Graphical abstract: Image 1 Highlights: Chinese dry-cured boneless hams with different quality grades (GS, NS and WS) were firstly investigated. Aldehydes, esters and furans were responsible for the quality variations of Chinese dry-cured boneless ham. Phospholipase and microorganism activities caused flavor differences of dry-cured boneless ham. Penicillium and Aspergillus were key microorganisms responded to volatiles development. β-Lipoxidation and Strecker degradation were key metabolic pathways to develop flavor variations of dry-cured boneless ham.